2013
DOI: 10.1371/journal.pone.0059884
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and Comparative Profiling of miRNAs in Invasive Bemisia tabaci (Gennadius) B and Q

Abstract: BackgroundMicroRNAs (miRNAs) are small, conserved, non-coding RNAs that post-transcriptionally regulate gene expression. Bemisia tabaci (Gennadius) B and Q are two invasive and dominant whiteflies, and B. tabaci Q has been displacing B in China. Differences in biological traits (fecundity, host range, resistance to insecticides, etc.) as affected by miRNAs might be involved in the displacement. In this study, we performed high-throughput sequencing to identify miRNAs in B. tabaci B and Q.ResultsWe identified 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
21
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(26 citation statements)
references
References 88 publications
(94 reference statements)
4
21
1
Order By: Relevance
“…These longer sRNAs were indeed also observed in the whitefly nymphs (Figure 2). A similar sRNA length distribution has previously been found in adult whiteflies (Guo et al, 2013; Wang et al, 2016) and similar sized sRNAs (between 26 and 30 nts) have been reported for other insects e.g., cotton-melon aphid ( Aphis gossypii ) or the brown planthopper ( Nilaparvata lugens ; Chen et al, 2012; Sattar et al, 2012). These longer sRNAs are assumed to be Piwi-interacting RNAs (piRNAs) and are known to be a large class of non-coding RNAs in animals, specifically linked to genome stability in germ-line cells and silence transposons (Vagin et al, 2006).…”
Section: Discussionsupporting
confidence: 82%
See 4 more Smart Citations
“…These longer sRNAs were indeed also observed in the whitefly nymphs (Figure 2). A similar sRNA length distribution has previously been found in adult whiteflies (Guo et al, 2013; Wang et al, 2016) and similar sized sRNAs (between 26 and 30 nts) have been reported for other insects e.g., cotton-melon aphid ( Aphis gossypii ) or the brown planthopper ( Nilaparvata lugens ; Chen et al, 2012; Sattar et al, 2012). These longer sRNAs are assumed to be Piwi-interacting RNAs (piRNAs) and are known to be a large class of non-coding RNAs in animals, specifically linked to genome stability in germ-line cells and silence transposons (Vagin et al, 2006).…”
Section: Discussionsupporting
confidence: 82%
“…LC, control leaflets (not infested with whitefly nymphs); LW, leaflets first infested with whiteflies but with adults and nymphs subsequently removed; LE, leaflets with whitefly eggs; WN, whitefly nymphs; PC, phloem control (not infested); PW, phloem infested with whitefly nymphs. Insets for LW, WN, and PW represent the size distributions and percentages of the sRNAs matching previously described whitefly miRNAs (Guo et al, 2013). …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations